Tüketicilerde Utangaçlık Düzeylerinin Demografik Özelliklerle İlişkisi. - KAYAN, Fahrettin (Journal of Abant Social Sciences / Abant Sosyal Bilimler Dergisi, 2026)
The aim of this study is to determine the levels of consumer shyness among young consumers aged between 18 and 33, examine the relationship of these levels with demographic variables, and group individuals with similar attitudes using cluster analysis. The study follows a quantitative design, and data were collected from 431 participants through a face-to-face survey using a convenience sampling method. In the analysis process, cluster analysis was conducted first, followed by a MANOVA test. The findings indicate that young consumers were divided into two distinct clusters based on their levels of shyness, with statistically significant differences observed between the clusters. Age and gender were variables explaining the differentiation between clusters, whereas no differences were found according to education or occupational groups. Mean scores reveal that the first cluster exhibits higher shyness levels than the second cluster. The study concretizes the young consumer profile by evaluating consumer shyness-based segmentation in a holistic manner alongside demographic dimensions.